2011
DOI: 10.1007/s00261-011-9796-8
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced ultrasound in abdominal imaging

Abstract: The administration of a contrast agent is considered an essential tool to evaluate abdominal diseases using Ultrasound. The most targeted organ is the liver, especially to characterize focal liver lesions and to assess the response to percutaneous treatment. However, the expanding abdominal indications of contrast-enhanced ultrasound make this technique an important tool in the assessment of organ perfusion including the evaluation of ischemic, traumatic, and inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 127 publications
2
26
0
Order By: Relevance
“…Since the advent of the contrast enhanced sonography (CEUS) in the early 1980s, many studies have shown the potential of this methodology in different fields of medical imaging [1, 2]. Inspired by successes in imaging the liver, efforts have been made by several researchers to test the utility of this technique in the evaluation of the kidney [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of the contrast enhanced sonography (CEUS) in the early 1980s, many studies have shown the potential of this methodology in different fields of medical imaging [1, 2]. Inspired by successes in imaging the liver, efforts have been made by several researchers to test the utility of this technique in the evaluation of the kidney [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ultrasound (CUS) is a readily available, inexpensive, non-invasive, and non-ionizing imaging modality to detect renal masses, but it has limited use when attempting to differentiate between RCC and renal angiomyolipoma (AML). A safe and accurate imaging modality is needed to differentiate between RCC and AML, and contrastenhanced ultrasound (CEUS) using microbubble-based contrast agents has garnered increasing attention in this regard (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…The recently developed technique of CEUS has markedly expanded the possibilities for sonographic hemodynamic studies. The technique involves the intravenous administration of minute, gas-filled microbubbles that strongly enhance intravascular flow signals 1012. Measurement of hepatic vein arrival (transit) times (HVAT or HVTT) using a microbubble agent, such as Levovist (Schering AG, Berlin, Germany), SonoVue (Bracco SpA, Milan, Italy), or Sonazoid (GE Healthcare, Oslo, Norway) has been suggested as an ultrasound-based technique to assess the degree of hepatic fibrosis based on the hypothesis that the arrival time of the injected microbubble would be shortened in cirrhosis due to hemodynamic abnormalities, such as arteriovenous shunting or capillarization of the sinusoid 2,3,11,12…”
Section: Introductionmentioning
confidence: 99%